Emerging markets bond index performance and sovereign default: The case of Ecuador - Wladimir Zanoni; Emily Díaz; Jorge Paredes; Leandro Andrián; Juan Lorenzo Maldonado (Inter-American Development Bank (IDB), 2024)
This paper delves into the dynamic impact of Ecuador's 2008 sovereign debt default on the subsequent performance of the country's bonds, specifically as measured by the Emerging Markets Bond Index (EMBI). Through a blend of qualitative and quantitative analyses, the paper develops a framework for understanding the interplay between macroeconomic and political fundamentals, global liquidity dynamics, and investor behaviors. Employing a synthetic control method, the study assesses the default's impact on Ecuador's EMBI performance, revealing a dynamically heterogeneous influence that fluctuates with evolving macroeconomic and political landscapes. The findings highlight the importance of considering a broad spectrum of economic variables in sovereign risk assessment, especially for economies with significant exposure to volatile commodity markets. The study offers insights into the complex dynamics governing sovereign bond markets post default, emphasizing the roles of fiscal discipline, investor communication, and political stability in mitigating sovereign risk.
Keywords: F34; G15; H63; F65; E44; 330; Sovereign Debt Default; EMBI; Fiscal Distress Analysis; Investor Behavior Dynamics; Ecuadorian Economic Policy